Direct Fermentation of Gelatinised Sago Starch to Solvent (Acetone Butanol-Ethanol) by Clostridium Acetobutylicum P262 - Md Salleh, Madihah (2002)
Several approaches have been applied for the improvement of direct fermentation of sago starch to solvent by C. acetobutylicum. Optimization of medium based on gelatinised sago starch as a carbon source and kinetics of solvent-yielding batch fermentation of individual sugars and their mixture derived from enzymatic hydrolysis of sago starch were carried out using batch fermentation in Scoth bottle. Development of pH control strategy for improvement of solvent production was carried out in batch fermentation using 2 L stirred tank fermenter. The data gathered from batch fermentation were used for development of models to describe direct fermentation of sago starch to solvent. The 2 L and 0.5 L stirred tank fermenter were used to investigate the feasibility of using continuous culture (single stage and two stage) on the improvement of direct fermentation of sago starch to solvent. In all modes of fermentation investigated, the activities of enzymes relevant to solvent fermentation (crotonase, thiolase, phosphate butyryltransferase and β-hydroxybutyryl-CoA dehydrogenase) were determined in order to find their relationship with acid and solvent production. The use of 30 g/L gelatinised sago starch as the sole carbon source produced 11.2 gIL total solvent i.e. 1.5-2 times higher than fermentation using pure maltose or glucose. Enzymatic pretreatment of gelatinised sago starch yielding maltose and glucose hydrolysate prior to the fermentation did not improve solvent production as compared to direct fermentation of gelatinised sago starch. The inefficiency of the amylolytic enzymes secreted during the fermentation in hydrolyzing starch to maltose and glucose is the main problem in direct fermentation of sago starch to solvent. The a-amylase and glucoamylase of C. acetobutylicum have different pH and temperature optima. The pH optima for a-amylase and glucoamylase were found to be at 5.3 and 4.0-4.4, respectively. a-amylase showed a broad pH stability profile, retaining more than 80% of its maximum activity at pH 3.0-8.0 after 24 h incubation at 37°C. However, glucoamylase was only stable at pH 4.0-5.0, maintaining more than 90% of its maximum activity after 24b incubation at 37°C. Production of solvent (11.0 g/L) in fermentation using 30 g/L sago starch was comparable to fermentation using corn starch and about two times higher than fermentation using potato and cassava starches. At the range of sago starch concentration investigated (10 to 80 g/L), the highest solvent production (18.8 g/L) was obtained at 50 g/L. A mixture of yeast extract and ammoniwn nitrate produced total solvent (18.8 g/L) of about 6 times higher than that produced by fermentation using yeast extract alone. The individual concentration of nitrogen and carbon influenced solvent production to a greater extent than carbon to nitrogen (C/N) ratio. Simple unstructured models employing Logistic and Leudeking-Piret equations were found sufficient to describe the growth of C. acetobutybcum and the production of acid and solvent. In fermentation without pH controL initial culture pH 6 gave the highest solvent production (14.13 g/L) with the overall productivity of 0.5 g/L/h. Growth of C. acetoburylicum, rate of starch hydrolysis and solvent production were greatly reduced in fermentation where pH was controlled at 4.5 during acidogenic phase. Excessive acid production (32 g/L) was obtained in fermentation where pH was controlled at 6.0 during the acidogenic phase which reduced solvent production significantly (7.1 g/L). In order to reduce acid accumulation, the fermentation where pH was allowed to decrease naturally by self-acidification during acidogenic phase was suggested. Solvent production was also reduced when pH during the solventogenic phase was controlled at 6.5. Substantial improvement of solvent production was achieved in fermentation where pH was not controlled during acidogenic phase (initial culture pH was 6) and then the pH was controlled at 5.5 during solventogenic phase. Using this pH control strategy, the overall productivity (0.79 g/L.h) was improved by 1.6 times as compared to fermentation without pH control, though the final solvent concentration (16.82 g/L) was about the same. The highest crotonase and phosphate butyryltransferase activity was observed in fermentation where pH was controlled at 5 during acidogenic phase, which was corresponded to fairly high acid production but low solvent production. On the other hand, specific activity of β-hydroxybutyryl-CoA was the highest at pH 5.5, which was corresponded to high acid and solvent production. In fermentation with controlled pH during solventogenic phase, the highest thiolase specific activity was obtained at pH 5.25, which was corresponded to the highest production of acetone. On the other hand, the highest specific activity of crotonase, β-hydroxybutyryl-CoA dehydrogenase and phosphate butyryltransferase was observed at pH 5.5, and this was corresponded to the highest production of ethanol and butanol.